Dark Tide II : Ruin - Stackpole, Michael A. (London Arrow Books, 2000)
Now, in a climate of mistrust - especially of the Jedi - Leia cannot convince the New Republic that the threat may not be over, even as the next wave of alien warships are entering the galaxy. It is up to Leia, Luke, the Solo Kids - Jedi Knights all - and the few who believe to defend the Outer Rim planets from invasion.
Keywords: Star Wars fiction -- Skywalker, Luke (Fictitious character) -- Solo, Han (Fictitious character)